2000
DOI: 10.4049/jimmunol.165.2.710
|View full text |Cite
|
Sign up to set email alerts
|

Human Uveal Melanoma Cells Produce Macrophage Migration-Inhibitory Factor to Prevent Lysis by NK Cells

Abstract: Human uveal melanoma arises in an immune privileged ocular environment in which both adaptive and innate immune effector mechanisms are suppressed. Uveal melanoma is the most common intraocular tumor in adults and is derived from tissues in the eye that produce macrophage migration-inhibitory factor (MIF), a cytokine that has recently been demonstrated to produce immediate inhibition of NK cell-mediated lytic activity. Although NK cell-mediated lysis of uveal melanomas is inhibited in the eye, melanoma cells t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
115
0
2

Year Published

2002
2002
2009
2009

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(119 citation statements)
references
References 31 publications
2
115
0
2
Order By: Relevance
“…3). NK cell-mediated killing of UM lines has been previously shown to be inhibited by factors secreted from tumor cells (30). However, conditioned culture supernatants of UM lines did not affect the viability or cytotoxic activity of the effectors used in our study (data not shown), consistent with the results of the cold target inhibition assays.…”
Section: Ifn␥-treated Um Cells Do Not Exert Negative Effects On Activsupporting
confidence: 91%
“…3). NK cell-mediated killing of UM lines has been previously shown to be inhibited by factors secreted from tumor cells (30). However, conditioned culture supernatants of UM lines did not affect the viability or cytotoxic activity of the effectors used in our study (data not shown), consistent with the results of the cold target inhibition assays.…”
Section: Ifn␥-treated Um Cells Do Not Exert Negative Effects On Activsupporting
confidence: 91%
“…Both cell lines are also characterized by higher basal MIF levels than normal cells. This phenomenon of enhanced MIF expression in tumor cells has recently been described in a series of studies and has been correlated with MIF's property of promoting tumor progression and angiogenesis (10,20,30,33).…”
Section: Discussionmentioning
confidence: 66%
“…Haplotypes and clinical features of the patients are reported in Table 1. The primary human uveal melanoma cell lines OM431 (34) and OCM1 (35); the liver metastatic human uveal melanoma cell lines OMM1 (36) and OMM2.3 (37); and the B6-derived murine melanoma cell lines B16, B16F0, B16F10 and the MT/ret melanoma cells, a kind gift of A. Prevost-Blondel (Institut Cochin, Paris, France) (24) were all cultured in RPMI 1640 medium/5% FCS/2 mM l-glutamine/50 μM 2-mercaptoethanol in a 5% CO2 humidified atmosphere at 37°C. All tumor cells were used for assays within 1 hour of collection, and viability was always greater than 95% as determined by Trypan blue exclusion.…”
Section: Discussionmentioning
confidence: 99%